2009
DOI: 10.1111/j.1749-6632.2008.03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Human Brain following Vestibular Neuritis Indicate Central Vestibular Compensation

Abstract: Vestibular neuritis (VN) is a sudden unilateral vestibular failure (UVF) with a variable course. Caloric hyporesponsiveness often persists, and it is largely unknown why patients with the same degree of hyporesponsiveness show different functional recovery. As the peripheral vestibular deficit alone does not seem to determine functional recovery, it was the aim of this study to elucidate whether structural (morphological) brain changes (1) contribute to central vestibular compensation, and (2) account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 48 publications
7
83
0
1
Order By: Relevance
“…As well, previous study on this subject has shown that maintenance of symmetric head rotation with EMG monitoring produce reliably reproducible results, the VEMP amplitude being the best criteria [20]. On the other hand, significant structural cortical alterations related to central vestibular compensation are observed in patients following acute vestibular lesions [21]. Conventional vestibular testing, however, focuses on reflex responses and therefore provides little insight into the functioning of the substantial vestibulo-cortical projection-responsible for sensations of rotation and vertigo [22].…”
Section: Discussionmentioning
confidence: 89%
“…As well, previous study on this subject has shown that maintenance of symmetric head rotation with EMG monitoring produce reliably reproducible results, the VEMP amplitude being the best criteria [20]. On the other hand, significant structural cortical alterations related to central vestibular compensation are observed in patients following acute vestibular lesions [21]. Conventional vestibular testing, however, focuses on reflex responses and therefore provides little insight into the functioning of the substantial vestibulo-cortical projection-responsible for sensations of rotation and vertigo [22].…”
Section: Discussionmentioning
confidence: 89%
“…Neuro-otological sig3ns of vestibular imbalance were assessed in a standardised fashion using a clinical vestibular score (CVS) 10. This score is based on clinical examination covering (1) spontaneous nystagmus, (2) head-shaking nystagmus, (3) gaze-evoked nystagmus, (4) positional nystagmus, (5) head impulse test,22 (6) ataxia of stance, (7) lateropulsion, (8) lateropulsion during gait without horizontal head movements, (9) ataxia of gait with horizontal head movements, (10) tandem gait ataxia, (11) ataxia on body rotation (180°) and (12) the Fukuda stepping test.…”
Section: Methodsmentioning
confidence: 99%
“…All high-resolution anatomical 3D images were acquired, preprocessed and analysed, as described elsewhere 10. T1-weighted three-dimensional gradient echos acquired with a fast low-angle shot sequence (FLASH) (TR=15 ms, TE=5 ms, flip angle 30°, acquisition matrix 256×256, isotropic voxel=1 mm 3 ) were acquired on a 1.5 T scanner (Siemens Symphony, Erlangen, Germany) with a standard head coil to reduce possible inhomogeneities and geometric variations due to magnetic field and gradient differences.…”
Section: Methodsmentioning
confidence: 99%
“…Three months after acute vestibular neuritis, voxel-based morphometry of MR-images demonstrated gray-matter volume increases within the multisensory vestibular cortical areas (insula, inferior parietal lobe, superior temporal gyrus), the cerebellum and motion-sensitive areas such as the middle temporal area MT /V5 [67]. At the same time, gray-matter volume decreases were found in the midline pontomedullary junction (i.e.…”
Section: Recovery Assessed By Functional and Structural Brain Imagingmentioning
confidence: 79%
“…the inhibitory brainstem commissural pathways interconnecting the MVN), which may either be a consequence of peripheral vestibular denervation or resulting from VC in order to rebalance the commissural inhibitory system. Taking into account that in this study a link between the amount of graymatter volume increase in the vestibular cortical areas and the decrease in vestibular complaints / deficits could be established, it suggests that the structural (volumetric) alterations found indeed reflect VC [67]. Except for gray-matter volume increases in the medial temporal gyrus bilaterally, gray-matter volume changes were not related to the degree of the peripheral vestibular deficit.…”
Section: Recovery Assessed By Functional and Structural Brain Imagingmentioning
confidence: 99%